THE ANALYSIS OF THE ARTISTIC AND GRAPHIC DESIGN OF THE HUMOROUS MAGAZINE «BALDA» IN THE CONTEXT OF SPECIALIZED EDITIONS OF THE EARLY TWENTIETH CENTURY - Svetlana N. Sheveleva (Russian Studies in Culture and Society)
The article presents an analysis of the artistic and graphic design of the only satirical and caricature magazine of printing and bookbinding workers «Balda» published in Russia. As result of the all the published issues, the reader’s address of the magazine was identified, as well as its technical characteristics were determined. After studying all three issues of the magazine, it was revealed how much textual information was printed, how much textual information was accompanied by drawings and how many percent of the magazine contained drawings as independent material. The features of graphic and compositional techniques used in the design of the magazine are analyzed. The article identifies the main features of the title complex “Baldy”, describes the fonts used. Fonts definitely have which group they belong to, font size, font type, density, saturation. The graphic and decorative elements used in the design of the magazine are described, with the help of which its original and memorable style is formed.